A Systematic Review of Metabolic Alterations Underlying IgE‐Mediated Food Allergy in Children. Issue 23 (20th October 2021) - De Paepe, Ellen; Van Gijseghem, Lynn; De Spiegeleer, Margot; Cox, Eric; Vanhaecke, Lynn
Abstract : Scope: Immunoglobulin E‐mediated food allergies (IgE‐FA) are characterized by an ever‐increasing prevalence, currently reaching up to 10.4% of children in the European Union. Metabolomics has the potential to provide a deeper understanding of the pathogenic mechanisms behind IgE‐FA. Methods and Results: In this work, literature is systematically searched using Web of Science, PubMed, Scopus, and Embase, from January 2010 until May 2021, including human and animal metabolomic studies on multiple biofluids (urine, blood, feces). In total, 15 studies on IgE‐FA are retained and a dataset of 277 potential biomarkers is compiled for in‐depth pathway mapping. Decreased indoleamine 2, 3‐dioxygenase‐1 (IDO‐ 1) activity is hypothesized due to altered plasma levels of tryptophan and its metabolites in IgE‐FA children. In feces of children prior to IgE‐FA, aberrant metabolization of sphingolipids and histidine is noted. Decreased fecal levels of (branched) short chain fatty acids ((B)SCFAs) compel a shift towards aerobic glycolysis and suggest dysbiosis, associated with an immune system shift towards T‐helper 2 (Th2) responses. During animal anaphylaxis, a similar switch towards glycolysis is observed, combined with increased ketogenic pathways. Additionally, altered histidine, purine, pyrimidine, and lipid pathways are observed. Conclusion: To conclude, this work confirms the unprecedented opportunities of metabolomics and supports the in‐depth pathophysiological qualification in the quest towards improved diagnostic and prognostic biomarkers for IgE‐FA. Abstract : A systematic review of Immunoglobulin E‐mediated food allergies (IgE‐FA) in childred revealed a shift in energy metabolism towards glycolysis and increased ketone body formation. Moreover, IgE‐FA was associated with aberrant metabolization of lipids, nucleotides, and amino acids, the latter including tryptophan metabolism due to decreased IDO‐1 activity in the case of Th2 immunity. Also, decreased levels of fecal SCFAs and altered bile metabolization pointed towards dysbiosis.